Effectiveness of Principal Supervision for Teacher Professional Competence - Hardiyanti, Menik; Madjid, Muh. Naim (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to determine the efforts used by school principals to improve eachers' professional competence, as well as the obstacles faced by school principals. The research method used is descriptive qualitative. The results showed that the school principal made efforts to improve the professional competence of teachers through academic supervision, providing training, workshops, and MGMP. However, there are still obstacles in the form of limited time and budget, as well as variations in teacher abilities. In conclusion, the active role of the school principal in carrying out supervision and coaching of teachers is very important to improve the professional competence of teachers.